2007
DOI: 10.1152/ajpregu.00798.2006
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of placental function alters heart development in the sheep fetus

Abstract: Placental insufficiency, resulting in restriction of fetal substrate supply, is a major cause of intrauterine growth restriction (IUGR) and increased neonatal morbidity. Fetal adaptations to placental restriction maintain the growth of key organs, including the heart, but the impact of these adaptations on individual cardiomyocytes is unknown. Placental and hence fetal growth restriction was induced in fetal sheep by removing the majority of caruncles in the ewe before mating (placental restriction, PR). Vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
206
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(223 citation statements)
references
References 55 publications
13
206
3
1
Order By: Relevance
“…Thus, the echo data was essential to determine whether valve integrity had been functionally compromised and provided information on placental blood flow that related to the intrauterine growth restriction (IUGR) that we observed. IUGR is associated generally with effects on placental and heart development (Corstius et al, 2005;Morrison et al, 2007). Other studies have reported that Wnt-β-catenin signaling and HCy impact placental development (Kamudhamas et al, 2004;Mohamed et al, 2008); our results substantiate these observations.…”
Section: Dmmbiologistsorg 474supporting
confidence: 90%
“…Thus, the echo data was essential to determine whether valve integrity had been functionally compromised and provided information on placental blood flow that related to the intrauterine growth restriction (IUGR) that we observed. IUGR is associated generally with effects on placental and heart development (Corstius et al, 2005;Morrison et al, 2007). Other studies have reported that Wnt-β-catenin signaling and HCy impact placental development (Kamudhamas et al, 2004;Mohamed et al, 2008); our results substantiate these observations.…”
Section: Dmmbiologistsorg 474supporting
confidence: 90%
“…However, this may not be the case following IUGR. Importantly, in this regard in the ovine model, where cardiomyocyte maturation resembles that in humans, we (Bubb et al, 2007) and others (Morrison et al, 2007) have shown delayed maturation of cardiomyocytes following induction of IUGR late in gestation. Hence, if this also applies to the human IUGR heart, it may be possible for ''catch-up'' hyperplasia to occur postnatally in a similar manner to that observed in the rodent heart.…”
Section: Discussionmentioning
confidence: 52%
“…Certainly, a reduction in the number of cardiomyocytes in early life could have an adverse impact on the heart's capacity for hypertrophy later in life. A significant reduction in the proportion of terminally differentiated cardiomyocytes has been shown in fetal sheep models of IUGR (Bubb et al, 2007;Morrison et al, 2007). In addition, recently, we have shown that the number of cardiomyocytes is significantly reduced at birth in rat offspring that had been exposed to maternal protein restriction (Corstius et al, 2005).…”
Section: Introductionmentioning
confidence: 73%
“…In the present study, we have used a well-established model of chronic placental insufficiency, in which the majority of the uterine caruncles (potential placental attachment sites) are removed prior to pregnancy in the sheep (1,18,23,50,54,55), which results in placental and, hence, fetal growth restriction, as well as chronic hypoxemia, from as early as measured from 100 days gestation (GA) (77). The growth-restricted placental restriction (PR) fetus has a relatively larger brain and adrenal gland and higher circulating norepinephrine and cortisol concentrations compared with the normally grown fetus in late gestation (48,67,77).…”
mentioning
confidence: 99%